An Examination of the Impact of Workplace Wellness Programs on Health Outcomes in the U.S. Versus European Countries - Clack, Lesley; Fraser, Warren (Journal of Organizational Psychology, 2019)
Non-communicable diseases are a growing concern for older adults, which has led to the popularity of wellness programs in developed countries to improve the health and productivity of workers. While the U.S. and Western Europe have invested a significant amount of money on wellness programs, trends indicate that the U.S. still falls short in health outcomes. This study utilized online databases to analyze data on each country’s average life expectancy and cardiovascular mortalities in comparison to prevalence of workplace wellness programs. Workplace wellness programs may be effective tools for impacting the health of a population once appropriate initiatives are incorporated.